3u-10=-6u+8

Simple and best practice solution for 3u-10=-6u+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3u-10=-6u+8 equation:



3u-10=-6u+8
We move all terms to the left:
3u-10-(-6u+8)=0
We get rid of parentheses
3u+6u-8-10=0
We add all the numbers together, and all the variables
9u-18=0
We move all terms containing u to the left, all other terms to the right
9u=18
u=18/9
u=2

See similar equations:

| 4÷3w-12=2÷3w | | 5q=-5+4q | | 6x+3=14x-3 | | 6-x=33 | | 7m-15=4m+9 | | -r-10=10+10-7r | | 4z/10-1=4 | | -8x+2x=92 | | 4x+5x-6=(3x-1) | | -6+4z=-2+3z | | x=400*(200+x)/(400+(200+x)) | | 1/x=1/400+1/(200+x) | | -9+x=-19 | | 7v+16=11v | | -2h=9-3h | | -9r-3=114 | | -g÷-6=-4 | | -10s+8=5s-7 | | 10n=7n+12 | | A=2w+3/16 | | 0.2x-1.8/5=4.2 | | -1=x-4/6 | | x/8+8=6 | | 21=t-9 | | -9-8b=55 | | -9s=-7s-6 | | n=-7+16 | | 5-x=12. | | 9p^2=6=42 | | -8-3j=-4j | | -7f=9-8f | | 6x+8x=2x |

Equations solver categories